Prevalence and dynamic changes of vagotonic T waves during exercise in elite soccer player population - Cárdenes León, A.; Garcia Salvador, J. J.; Quintana Casanova, C. A.; Medina Fernández Aceytuno, A. (Archivos de medicina del deporte, 2018)
Introduction: The characteristics of the athlete`s electrocardiogram are still today the subject of multiple publications whose physiological meaning has been clarified as the different variants have been correlated with a sophisticated cardiological evaluation and a prolonged follow-up. There are different alterations of repolarization described in the sports population, among them the most frequently reported in the literature are: early repolarization, vagotonic T waves, ST-T alterations, etc. Vagotonic T waves are a common finding in the athlete population, although currently, the dynamic changes of this finding during exercise, have an uncertain meaning. The aim of our study was to determine its prevalence in a population of elite athletes and analyze their behavior at different stages of the exercise.